Application of Gemstone Spectral Computed Tomography Imaging in the Characterization of Solitary Pulmonary Nodules: Preliminary Result. Issue 6 (November 2016) - Lin, Ji-zheng; Zhang, Liang; Zhang, Chuan-yu; Yang, Lei; Lou, He-nan; Wang, Ze-guo
Abstract : Objective: This study aimed to observe the value of computed tomography (CT) spectral imaging parameters in the diagnosis of solitary pulmonary nodules, during the contrast-enhanced early phase and late phase. Materials and Methods: This study was approved by the institutional review board and written informed consent was obtained from all patients. One hundred thirty-nine patients with solitary pulmonary nodules proved by pathology underwent double-phase enhanced CT scan using gemstone spectral imaging mode on a Discovery CT750 HD, and were divided into an active inflammatory group (43 cases), a malignant group (65 cases), and a tuberculosis group (31 cases). The slope rate was calculated from the spectral curve. Iodine concentrations (ICs) were derived from iodine-based material decomposition CT images and normalized to the IC in the aorta. The Kruskal–Wallis test and Nemenyi test were performed to compare quantitative parameters among the 3 groups or between each of the 2 groups. Results: There were significant differences in the slope rate, IC, and normalized IC (NIC) among the 3 groups. In the active inflammatory group, malignant group, and tuberculosis group, the mean slope rate were 3.03 ± 0.71 (SD), 1.96 ± 0.91, and 1.37 ± 0.43, respectively, during the early phase and 3.28 ± 0.67, 2.24 ± 0.82, and 1.67 ± 0.64, respectively, during the late phase. The ICs were 2.68 mg/mL ± 0.56, 1.65 mg/mL ± 0.76, and 1.10 mg/mL ± 0.34, respectively, during the early phase and 2.79 mg/mL ± 0.57, 1.90 mg/mL ± 0.71, and 1.29 mg/mL ± 0.44, respectively, during the late phase. The NIC were 0.24 ± 0.06, 0.16 ± 0.04, and 0.10 ± 0.04, respectively, during the early phase and 0.57 ± 0.10, 0.43 ± 0.11, and 0.25 ± 0.09, respectively, during the late phase. The mean slope rate, IC, and NIC for the active inflammatory group were significantly higher than these parameters for the malignant group ( P < 0.05), and the parameters for malignant group were significantly higher than the tuberculosis group ( P < 0.05). Conclusions: Dual-energy CT gemstone spectral imaging provides a novel method to better characterize pulmonary nodules in double-phase contrast-enhanced scanning.